Peran Ibu dalam Pemenuhan Hak Anak terhadap Gizi Seimbang - 10030220026, Nisa Nurrizka Hidayat; Nan Rahminawati; Sobar Al Ghazal (UNISBA Press, 2024)
Abstract. Child undernutrition impacts current and future health. Factors contributing to undernutrition status in children under five include inadequate nutrient intake and complex issues involving unbalanced diets, parenting, poor sanitation, limited access to health services, and other environmental factors that contribute to stunting. Interestingly, stunting can occur even though children are born with normal weight if nutrition intake is insufficient. The role of mothers is very important in meeting the nutritional needs of children, to support optimal growth and development. Based on this phenomenon, the problems in this study are formulated as follows: (1) What are the rights of children given by mothers in fulfilling balanced nutrition for 3-4 years old with malnutrition status at Posyandu Anggrek RW 02 Cicadas Kota Bandung? (2) How are the obligations of mothers in fulfilling balanced nutrition for children aged 3-4 years with malnutrition status at Posyandu Anggek RW 02 Cicadas Kota Bandung? Researchers used a case study method with a qualitative approach. The data collection techniques used in this research are interviews, observation, and documentation. The data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of this study are: Children's right to balanced nutrition has not been fully fulfilled. Some mothers have difficulties in providing nutritious food every day, differences in children's interest in healthy food, irregularity in providing nutritious food, and limited consultation with doctors or nutritionists can affect the fulfillment of children's rights to adequate and quality nutritional intake every day. Abstrak. Kekurangan gizi pada anak berdampak pada kesehatan saat ini dan masa depan. Faktor penyebab status gizi kurang pada balita meliputi asupan nutrisi yang tidak mencukupi dan masalah yang kompleks melibatkan pola makan tidak seimbang, pola asuh, sanitasi buruk, akses terbatas layanan kesehatan, dan faktor lingkungan lainnya yang berkontribusi terhadap kejadian stunting. Menariknya stunting dapat terjadi meski anak lahir dengan berat badan normal jika asupan gizi tidak mencukupi. Peran ibu sangat penting dalam memenuhi kebutuhan gizi anak, untuk mendukung tumbuh kembang yang optimal. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apa saja hak anak yang diberikan ibu dalam memenuhi gizi seimbang usia 3-4 tahun yang berstatus gizi kurang di Posyandu Anggrek RW 02 Cicadas Kota Bandung? (2) Bagaimana kewajiban ibu dalam memenuhi gizi seimbang anak usia 3-4 tahun yang berstatus gizi kurang di Posyandu Anggek RW 02 Cicadas Kota Bandung?. Peneliti menggunakan metode studi kasus dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara, observasi, dan dokumentasi. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah: Hak anak untuk mendapatkan gizi seimbang belum sepenuhnya terpenuhi. Beberapa ibu memiliki kesulitan dalam menyediakan makanan bergizi setiap hari, perbedaan minat anak terhadap makanan sehat, ketidakteraturan dalam penyediaan makanan bergizi, serta keterbatasan konsultasi dengan dokter atau ahli gizi dapat memengaruhi pemenuhan hak anak atas asupan gizi yang memadai dan berkualitas setiap hari.